2006
DOI: 10.1111/j.1600-6143.2006.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+25+ Regulatory T Cells Limit Th1-Autoimmunity by Inducing IL-10 Producing T Cells Following Human Lung Transplantation

Abstract: Chronic human lung allograft rejection is manifested by bronchiolitis obliterans syndrome (BOS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 57 publications
3
110
0
1
Order By: Relevance
“…Therefore, we must consider the unique collaboration that exists between human memory Th-17 cells and CD14 1 macrophages as a possible link between adaptive and innate immunity. Bharat and colleagues, using PBMCs from patients who had received a lung transplant, demonstrated a key role for immune regulation by CD4 1 CD25 1 T-regulatory cells in preventing outgrowth of col(V)-reactive Th-1 (IFN-g) effector cells in long-term cultures (31,32). However, this report did not address the mechanisms of T-effector function in vivo or the role of IL-17.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, we must consider the unique collaboration that exists between human memory Th-17 cells and CD14 1 macrophages as a possible link between adaptive and innate immunity. Bharat and colleagues, using PBMCs from patients who had received a lung transplant, demonstrated a key role for immune regulation by CD4 1 CD25 1 T-regulatory cells in preventing outgrowth of col(V)-reactive Th-1 (IFN-g) effector cells in long-term cultures (31,32). However, this report did not address the mechanisms of T-effector function in vivo or the role of IL-17.…”
Section: Discussionmentioning
confidence: 81%
“…Recent studies by Wilkes have demonstrated that immune responses against collagen V, an auto-Ag, can induce obliterative airway disease in rats following lung transplantation (32) and may also play a pathogenic role in BOS following human lung transplantation. Our studies have shown that collagen V-reactive cells develop during post-lung transplantation in humans and they are regulated by IL-10-producing T regulatory cells (35). The inflammatory status observed during the development of BOS in these patients could also result in the development of polyreactive Abs that recognize the self-Ags.…”
Section: Discussionmentioning
confidence: 98%
“…Islets from murine pancreata were isolated and transplanted as described in our earlier publicaions (18,19 (20,21 (22). …”
Section: Mouse Islet Isolation Transplant and Immunosuppressionmentioning
confidence: 99%